F-Test and Analysis of Variance (ANOVA) in Economics - Kumar, Nand Kishor (Darul Yasin Al Sys, 2024)
ANOVA remains a cornerstone of empirical economic research, providing economists with a robust framework to analyze differences between groups, eval_uate policy interventions, and draw meaningful conclusions from data. Its versatility and applicability across diverse economic contexts underscore its significance in advancing economic theory and informing evidence-based policymaking. As data availability and computational capabilities continue to expand, ANOVA's role in economic analysis is expected to evolve, supporting increasingly sophisticated studies of economic phenomena and policy impacts. In economics, particularly in empirical research and data analysis, the F-test and Analysis of Variance (ANOVA) are fundamental statistical tools used to test hypotheses regarding the equality of means across two or more groups.